A depositional history of particulate organic carbon in a floodplain lake from the lower Ob’ River, Siberia - Dickens, Angela F.; Baldock, Jeff; Kenna, Timothy C.; Eglinton, Timothy I. (Geochimica et Cosmochimica Acta, 2011)
Northern, high latitude soils have stored vast amounts of organic carbon (OC) in permafrost and peats for many millennia, however, climate change may mobilize and release this particulate OC (POC) to arctic rivers. Deltaic and floodplain lakes that receive fluvial sediments, primarily during the spring freshet, may provide records of such changes in riverine POC. Here, we examine properties of OC in a sediment core from a lake in the lower floodplain of the Ob’ River, west Siberia, to determine how the properties of OC deposited in this lake varied over many decades and to evaluate use of this sedimentary OC as a recorder of riverine POC load and properties. The core predates the most recent, dramatic changes in arctic climate and hence may serve as a benchmark against which to contrast future variations in fluvial POC discharge. Elemental, stable carbon and radiocarbon isotopic analyses, along with nuclear magnetic resonance (NMR) spectroscopy and molecular-level information (lignin phenol composition), indicate two major sources of OC to most of the sediments in this lake: plant-derived OC and algal-derived OC. However, a mixing model indicates that the nature and 14C content of these two sources change with depth in the sediment, resulting in three distinct layers: surface horizons, a “high-OC” layer and “mixing” horizons found above and below the high-OC layer. The plant-derived component is significantly aged throughout the core (14C ages of 1300–3900 years) and appears to derive from primarily local, tundra sources, whereas the algal component is modern. Our analysis suggests that the usual mode of OC deposition, as exemplified by the “mixing” and surface horizons, involved mixing of varying amounts of new algal production (35–65%) with aged permafrost- or peat-derived OC. This deposition was interrupted by an event, such as the collapse of a riverbank, which laid down the compositionally distinct “high-OC” layer in which plant-derived OC mixes with aged mineral-soil-derived OC without clear input from algae. The relative amounts of the plant and algal components in the lake sediments appear to be controlled primarily by local hydrological conditions rather than by river-wide processes, suggesting that comparison of sediment records from multiple lakes within a floodplain will be important to assess changes in POC export by arctic rivers. However, the flux and nature of the higher plant-derived OC may carry important information on the sources and dynamics of OC stored within the drainage basin.
id: 2172